2008
DOI: 10.1016/j.engstruct.2007.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Significance of SSI and nonuniform near-fault ground motions in bridge response I: Effect on response with conventional expansion joint

Abstract: This paper studies the influence of spatially varying near-source ground motions and soil-structure interaction (SSI) on the relative response of two bridge frames. The spatial ground motions are simulated according to a near-fault ground motion model with different wave apparent velocity and a coherency loss function. Numerical calculations of bridge structure responses including pounding and SSI effect to a number of simulated spatially varying ground motions are carried out. The study reveals that the assum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(41 citation statements)
references
References 19 publications
0
40
0
1
Order By: Relevance
“…Pounding is an extremely complex phenomenon involving damage due to plastic deformation, local cracking, and fracturing due to impact, and friction when adjacent components are in contact with each other. To simplify the analysis, many researchers model a bridge girder as a lumped mass [Saiidi et al, 1996;Jankowski et al, 1998;Malhotra, 1998;DesRoches and Fenves, 2000;Ruangrassamee and Kawashima, 2001;DesRoches and Muthukumar, 2002;Jankowski, 2006a;Chouw and Hao, 2005, 2008a, 2008bGuo et al, 2009] or beam-column elements [Jankowski et al, 2000;Kawashima and Shoji, 2000;Ruangrassamee and Kawashima, 2003;Chouw et al, 2006;Ruiz Julian et al, 2007;Abdel Raheem, 2009;Mitoulis and Tegos, 2010] as shown in Figs. 2(a) and 2(b), respectively.…”
Section: Bridge Modelsmentioning
confidence: 99%
“…Pounding is an extremely complex phenomenon involving damage due to plastic deformation, local cracking, and fracturing due to impact, and friction when adjacent components are in contact with each other. To simplify the analysis, many researchers model a bridge girder as a lumped mass [Saiidi et al, 1996;Jankowski et al, 1998;Malhotra, 1998;DesRoches and Fenves, 2000;Ruangrassamee and Kawashima, 2001;DesRoches and Muthukumar, 2002;Jankowski, 2006a;Chouw and Hao, 2005, 2008a, 2008bGuo et al, 2009] or beam-column elements [Jankowski et al, 2000;Kawashima and Shoji, 2000;Ruangrassamee and Kawashima, 2003;Chouw et al, 2006;Ruiz Julian et al, 2007;Abdel Raheem, 2009;Mitoulis and Tegos, 2010] as shown in Figs. 2(a) and 2(b), respectively.…”
Section: Bridge Modelsmentioning
confidence: 99%
“…Figure 2 shows the macro element model. The elastic stiffness of the 3DOF footing system can be calculated using the formulation described in Chouw and Hao [14]. …”
Section: Macro Element Modelmentioning
confidence: 99%
“…This equation was incorporated in a macro element model so that the response of structure with nonlinear SFSI can be calculated [13]. Chouw and Hao [14] also numerically studied and showed that SFSI can affect the pounding force between adjacent bridge structures.…”
Section: Introductionmentioning
confidence: 99%
“…[18,19]) revealed that soil-structure interaction (SSI) can further alter the bridge responses under earthquake loadings. Not to further complicate the problem, SSI is, however, not considered in the present study since the primary aim of this study is to investigate the influence of shear keys on the seismic induced pounding responses of bridge structures.…”
Section: Introductionmentioning
confidence: 99%